The right to a fair trial in the European Union: lights and shadows - Galera Rodrigo, Susana (Revista de Investigações Constitucionais, 2015)
This article is focused on one of the rights provided by the article 47 of the Charter of Fundamental Rights of the European Union: the right of a fair trial. It is not a new contribution of the Charter but a guarantee which has been provided by the EU Law for decades, first appeared as procedural right, later recognized as a general principle of the EU and finally embodied in the Charter. This work reminds such process of recognition, paying special attention to the judicial remedies provided by the EU law and to some specific rules which affect the environment on the right of a fair trial is developed. The article concludes underlining, on one hand, the improvements on the right to a fair trial carried out by this legal process and, on the other hand, a few gaps on the issue which are neither recent nor consistent with the effectiveness and completeness of such right as it is required by the Rule of Law tradition.